2001
DOI: 10.1002/1096-987x(200102)22:3<316::aid-jcc1004>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of base-catalyzed reactions between isocyanates and epoxides affording 2-oxazolidones and isocyanurates

Abstract: ABSTRACT:Title reactions were investigated with ab initio calculations.Methyl isocyanate and ethylene oxide were adopted as model reactants. The products, 2-oxazolidones and isocyanurates, cannot be yielded without a base catalyst. The 2-oxazolidone may be produced by a dual S N 2 reaction, where the catalyst base (e.g., Cl − ) is a nucleophile and a leaving group on the ethylene-oxide carbon. Isocyanurate is generated by the stepwise association of three isocyanate molecules, where one of the molecules is ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…Okumoto et al 107 studied model reactions through ab initio calculations to determine the main reactions pathways (Scheme 20). The 2-oxazolidone 9 is thought to be produced by a dual S N2 reaction, where the catalyst (e.g., Cl − ) is a nucleophile and a leaving group on the ethylene−oxide carbon.…”
Section: Oxazolidonementioning
confidence: 99%
“…Okumoto et al 107 studied model reactions through ab initio calculations to determine the main reactions pathways (Scheme 20). The 2-oxazolidone 9 is thought to be produced by a dual S N2 reaction, where the catalyst (e.g., Cl − ) is a nucleophile and a leaving group on the ethylene−oxide carbon.…”
Section: Oxazolidonementioning
confidence: 99%
“…In the case of zwitterion 2, a new chemical shift at lower field would be expected however it was not observed. Previous research has reported a lower activation energy of 14.6 kcal/mol for zwitterion 1 and 34.3 kcal/mol for zwitterion 2, which further supports that zwitterion 1 is the true initiating species for the polymerization. For nucleophiles with varied nucleophilicity, the stronger ones lead to faster formation of the initiating species, resulting in significantly reduced gel time.…”
Section: Resultsmentioning
confidence: 88%
“…The mechanisms of these catalytic processes have been investigated using density functional theory (DFT) methods. 3,16,17,20,21,26 All the DFT results suggest that the isocyanate cyclotrimerization processes are highly exothermic, which demonstrates that isocyanurates are quite thermodynamically stabilized molecules.…”
Section: Introductionmentioning
confidence: 95%